How Rural Women's Perception of their Empowerment - Yarmohammad Ghasemi; zahra azizi; hossein mahdizadeh (توسعه اجتماعی)
The present research intends to take this issue into the question that rural women have what perception of their empowerment. The research method is qualitative approach using grounded theory. The study population consists of rural women resident in 11 villages in the suburb of Ilam which is based on purposive sampling 30 of them were interviewed semi-structured. The strategy of data analysis is based on three-steps open coding axial and selective, which its product was drawn in a paradigmatic model. Accordingly, 35 concepts and 11 categories were obtained. Which basic theory in derived model is Hegemonic Discourse of Gender. According to this theory, studied rural women are encountered with obstacles such as closed economic system, lack of institutional support, lack of access to these centers and cultural barriers to their ability.